Perempuan Dan Politik; Antara Cita Dan Fakta Studi Atas Peran Perempuan Dalam Pembangunan Di Brunei Darussalam - Nuril Hidayati; Ashfa Fikriyah (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2016)
Discourse of the renowned on these women sub-ordinated are very representative of the conditions of women in many countries in Asia, Africa and the Middle East, but what about the women in Southeast Asia, especially Brunei Darussalam? The only one of absolute monarchy country remaining in the world today, in addition, Brunei is a country with Islam as the ideological foundation of his administration, but why not a lot of emerging news about womenâ€™s movements and upheavals from there? With Anthropological Social approach through the phenomenological method this study aimed to uncover the role and involvement of women in Brunei Darussalam development. Thus observations to Brunei Darussalam and interviews with women as well as state policy regulators become a vital tool for collecting data. The role of literature as good books, journals, magazines and others also cannot be denied. Testing the validity of the data will be done by triangulation and then described the events were â€œphotographedâ€ to get the pattern on the role and involvement of women in Brunei Darussalam development. This study successfully to show that everyday Brunei women life in shades of religious but not extremely considering the country use the washatiyah / moderate Shafiâ€™i schools as the state legal basis so that the general of the women have contributed in the public domain. All forms of political decisions is in the grip of the sovereign, however, women had a lot of influence in giving nuance to state policies. Thus the women need for actualize themselves was not entirely negated, as in many Islamic countries in the Middle East and Africa